TINJAUAN SOSIAL EKONOMI DESA BANGGA - Antuke, Yulyan; Bulo, Yulan; Mondong, Tonny Iskandar (Jambura History and Culture Journal, 2022)
In rural areas, the economy is very important, being the main factor in the growth and development of the village, as is the case with the proud village located in the Paguyaman coast sub-district, it is important to be able to review the village economy to be able to see what things need to be improved. Socio-economic conditions that are still lagging behind because the area is in the interior, making transportation access difficult. However, with the development of time the economy can be improved little by little with assistance from the government and the community who can manage the village, although the results are not too large but can support the village community's economy.